ON THE EXAMPLE OF THE EXPERIENCE OF DEVELOPED FOREIGN COUNTRIES ON THE STRUCTURE AND ORGANIZATION OF THE ROLE OF MANAGEMENT BOARDS IN HIGHER EDUCATION INSTITUTIONS - Yakubov Azizjon Tajiboevich (Western European Studies, 2024)
This article lays the groundwork for the study of the main principles and lessons learned from the governing boards of developed foreign countries and their impact on the management and leadership of higher education institutions
Keywords: educational institutions; foreign countries; management